2013
DOI: 10.1093/rpd/nct339
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation-based feasibility study of a dose-area product meter built into a collimator for diagnostic X-ray

Abstract: According to the International Electro-technical Commission, manufacturers of X-ray equipment should indicate the number of radiation doses to which a patient can be exposed. Dose-area product (DAP) meters are readily available devices that provide dose indices. Collimators are the most commonly employed radiation beam restrictors in X-ray equipment. DAP meters are attached to the lower surface of a collimator. A DAP meter consists of a chamber and electronics. This separation makes it difficult for operators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous studies have revealed that radiological technologists tend to take a radiograph with a higher exposure dose to avoid re-examination. Seo et al reported that the entrance surface dose (ESD) of a digital radiography system was 55.25% higher than that of the analog system in general radiographic examinations in Korea [ 2 , 5 ]. Therefore, it is essential to manage and control the exposure dose of the digital radiography system for patient safety regarding radiation protection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that radiological technologists tend to take a radiograph with a higher exposure dose to avoid re-examination. Seo et al reported that the entrance surface dose (ESD) of a digital radiography system was 55.25% higher than that of the analog system in general radiographic examinations in Korea [ 2 , 5 ]. Therefore, it is essential to manage and control the exposure dose of the digital radiography system for patient safety regarding radiation protection.…”
Section: Introductionmentioning
confidence: 99%
“…Since the digital radiography (DR) system was introduced in medical radiology, progress has been made in diagnostic imaging, such as obtaining a constant gray-level image regardless of the degree of X-ray exposure through digital image processing [ [1] , [2] , [3] ]. This is expected to reduce the medical radiation exposure of the public.…”
Section: Introductionmentioning
confidence: 99%